Developing A Differentiation Strategy of A Captive Insurance Companies Case Study of PT XYZ - Adriana, Dadi; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2013)
PT. XYZ (XYZ) is an Indonesian captive insurance company which provides various general insurance products. In this research, XYZâ€™s Â differentiation strategy will be crafted by going through the strategic management process by using SWOT and five forces analysis. Based on the result of the environment analysis, XYZâ€™s differentiation strategy are determined and discussed. In a nut shell, XYZâ€™s strategy is to â€œachieve its vision e.i. To be The Most Admired General Insurance Company by offering innovative risk protection solutions.â€ Â Keywords: captive insurance company strategy, strategic management, differentiation strategy.